Effects of Carbohydrates on Rosmarinic Acid Production and In Vitro Antimicrobial Activities in Hairy Root Cultures of Agastache rugosa - Hyeon Ji Yeo; Min Jae Kwon; Sang Yeon Han; Jae Cheol Jeong; Cha Young Kim; Sang Un Park; Chang Ha Park (Plants, 2023)
Agastache rugosa (popularly known as Korean mint) belongs to the Lamiaceae family and comprises 22 species of perennial aromatic medicinal species native to East Asian countries, such as Korea, Taiwan, Japan, and China. A. rugosa contains many phenolic compounds that exhibit pharmacological and physiological activities, including antioxidant, anticancer, antiviral, antifungal, and antibacterial activities. The highest concentrations of rosmarinic acid and its isomers have been reported in the roots of A. rugosa. In this in vitro study, hairy roots of A. rugosa were obtained and the carbohydrates (sorbitol, mannitol, glucose, maltose, galactose, mannose, and sucrose) were evaluated to determine those that were optimal for rosmarinic acid production and hairy root growth. Antioxidant and antibacterial activities of extracts of A. rugosa were also assessed. The best carbon source for A. rugosa hairy root cultures was sucrose, considering biomass productivity (0.460 ± 0.034 mg/30 mL), rosmarinic acid production (7.656 ± 0.407 mg/g dry weight), and total phenolic content (12.714 ± 0.202 mg/g gallic acid equivalent). Antioxidant and antimicrobial activities were displayed by A. rugosa hairy roots cultured in liquid medium supplemented with 100 mM sucrose. Twenty-five bacterial strains, including multidrug-resistant bacteria and one pathogenic yeast strain, were used for antimicrobial screening of A. rugosa hairy roots. The hairy root extracts displayed antibacterial activity against Micrococcus luteus (KCTC 3063) and Bacillus cereus (KCTC 3624). The inhibition of these bacteria was greater using A. rugosa hairy roots with the highest levels of phenolic compounds cultured in the presence of sucrose, compared to hairy roots with the lowest levels of phenolic compounds cultured in the presence of fructose. Considering hairy root biomass, phenolic compound production, and antibacterial activity, sucrose is the best carbon source for A. rugosa hairy root cultures.